Novel corona virus outbreak: learn a lesson from Prayag Raj Kumbh - Chaurasia, Rakesh Chandra (International Journal of Scientific Reports, 2020)
In December 2019, coronavirus again divert global attention. New coronavirus as first detected in Wuhan, Hubai Province, China has officially named novel coronavirus and designated as 2019 - n CoV. The deadly pneumonia outbreak associated with virus is a zoonotic disease, transmitted to persons from animals